Teorema de Pitágoras: uma proposta de ensino e aprendizagem para alunos deficientes visuais - Luiz, Nasael Martins (2018)
The purpose of this paper was to investigate the potentialities and limitations of a teaching intervention, structured on the basis of making materials to be handled by visually impaired students, aiming at the construction of Pythagorean Theorem concept, systematization and learning. The chosen theme is part of Geometry field which has strong association with visual experiences, and from the hypothesis that this public is able to appropriate notions related to this concept as well as the sighted, providing their access by other senses, considering their specificities and adaptations. This study proposed to answer the question: "What are the potentialities and limitations of a structured teaching intervention from tactile materials related to Pythagorean Theorem, for the first grade students with visual impairment?" And to answer it, a qualitative research was carried out through a case study, with two congenital blind pupils of public schools in Itapevi and Barueri, both in São Paulo. The students passed by the interventions which consisted on the application of seven activities using a representative depictions of polygons and specific instruments to measure and compare angles. The theoretical basis of this research was the study of Vygotsky's conceptions of the development of higher psychological functions through the observation of information transit (the thoughts) at the zone of proximal development of an individual. An overview of Brazilian legislation on inclusive education that theoretically approaches disabled people education, especially visual sensory, was also part of the elements that underpinned this study. The results showed that a mediation action of an experienced person aided with the manipulation of materials and structured activities within each students specificities, made possible the acquisition and development of knowledge related to Geometry by the students, to construct the concept of the Pythagorean Theorem. The curricular adaptation has contributed to an inclusion in which teaching and learning process prevails.